Site reliability engineering fundamentals (O'Reilly Media, Inc., 2021)
Over the past five years, the ideas behind site reliability engineering (SRE) have caught fire because of their success in improving the reliability of systems. But those just starting their SRE journey often have questions. For instance, how do you transform an existing organization toward SRE? Where do DevOps and SRE overlap, and where do they diverge? And which method for calculating and measuring service-level objectives (SLOs) should you use, and when? Join Incident Labs’ Emil Stolarsky and Jaime Woo to gain a foundational understanding of SRE principles and the infrastructure practices and processes of a range of organizations—along with actionable advice on putting them to work in your organization. Emil and Jaime will also take you through the pragmatic and sometimes messy decisions that must be made on a regular basis to form a functional and successful SRE culture.